2018
DOI: 10.2169/internalmedicine.1141-18
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Case of Familial Neuronal Intranuclear Inclusion Disease with Dementia and Neuropathy

Abstract: Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disease with marked variety in its clinical manifestations. While characteristic neuroimaging and skin biopsy findings are important clues to the diagnosis, autopsy studies are still important for confirming the exact disease features. We herein report the case of a patient who received an antemortem diagnosis of familial NIID with dementia-dominant phenotype that was later confirmed by an autopsy. Our report is the first to document a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Similarity has been found in the MRI findings between NIID and FXTAS and the presence of eosinophilic intranuclear inclusions [21,31,35].It is found that NIID shares a common molecular basis with FXTAS-a disease caused by mildly expanded CGG repeats (premutation) in the 5′ untranslated region (UTR) of FMR1, with 55-200 repeat units. [11] By TRhist technique [40] recently few researchers found accumulation of short reads filled with CGG repeats in the 5′ UTR of NBPF19 (NOTCH2NLC) in NIID.…”
Section: Neuronal Intranuclear Inclusion Disease (Niid)supporting
confidence: 69%
See 2 more Smart Citations
“…Similarity has been found in the MRI findings between NIID and FXTAS and the presence of eosinophilic intranuclear inclusions [21,31,35].It is found that NIID shares a common molecular basis with FXTAS-a disease caused by mildly expanded CGG repeats (premutation) in the 5′ untranslated region (UTR) of FMR1, with 55-200 repeat units. [11] By TRhist technique [40] recently few researchers found accumulation of short reads filled with CGG repeats in the 5′ UTR of NBPF19 (NOTCH2NLC) in NIID.…”
Section: Neuronal Intranuclear Inclusion Disease (Niid)supporting
confidence: 69%
“…NIID is a neurodegenerative disease characterized clinically by various combinations of cognitive decline, parkinsonism, cerebellar ataxia and peripheral neuropathy, and neuropathologically by eosinophilic hyaline intranuclear inclusions in the central and peripheral nervous systems as well as in other tissues including cardiovascular, digestive and urogenital organs [29,30,31,32] and age of onset usually ranges from infancy to late adulthood. An autosomal dominant mode of inheritance has been thought [33,34,35] of previously but about two thirds of cases have been reported to be sporadic in nature [31].…”
Section: Neuronal Intranuclear Inclusion Disease (Niid)mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the diagnosis of the 50 cases with NIID reviewed, 20 were confirmed by skin biopsy, 15 by autopsy, 10 by rectal biopsy, 1 by colon biopsy, 1 by both the skin and the rectal biopsy, and 3 reports made no mention of the pathology (Table ) . There were 31 patients with MRI records, including 23 patients with brain atrophy (23/31, 74.19%).…”
Section: Resultsmentioning
confidence: 99%
“…NIID is also known to have several ophthalmologic manifestations, such as miosis, night blindness, and reduced electroretinographic (ERG) responses, and retinal degenerative changes with onset at various ages. 11 15 Adult-onset NIID is often accompanied by miosis, and part of infantile- or juvenile-onset NIID is reported to be associated with nystagmus and eye movement disorders. 11 Although there are few reports on the retinal findings including the ERG findings, ERG abnormalities have been reported in all age groups.…”
mentioning
confidence: 99%